High hydrostatic pressure induces immunogenic cell death in human tumor cells - Fucikova, Jitka; Moserova, Irena; Truxova, Iva; Hermanova, Ivana; Vancurova, Irena; Partlova, Simona; Fialova, Anna; Sojka, Ludek; Cartron, Pierre-Francois; Houska, Milan; Rob, Lukas; Bartunkova, Jirina; et al. (International journal of cancer, 2014)
Recent studies have identified molecular events characteristic of immunogenic cell death (ICD), including surface exposure of calreticulin (CRT), the heat shock proteins HSP70 and HSP90, the release of high-mobility group box protein 1 (HMGB1) and the release of ATP from dying cells. We investigated the potential of high hydrostatic pressure (HHP) to induce ICD in human tumor cells. HHP induced the rapid expression of HSP70, HSP90 and CRT on the cell surface. HHP also induced the release of HMGB1 and ATP. The interaction of dendritic cells (DCs) with HHP-treated tumor cells led to a more rapid rate of DC phagocytosis, upregulation of CD83, CD86 and HLA-DR and the release of interleukin IL-6, IL-12p70 and TNF-α. DCs pulsed with tumor cells killed by HHP induced high numbers of tumor-specific T cells. DCs pulsed with HHP-treated tumor cells also induced the lowest number of regulatory T cells. In addition, we found that the key features of the endoplasmic reticulum stress-mediated apoptotic pathway, such as reactive oxygen species production, phosphorylation of the translation initiation factor eIF2α and activation of caspase-8, were activated by HHP treatment. Therefore, HHP acts as a reliable and potent inducer of ICD in human tumor cells.
Keywords: HLA-DR antigeny; Interleukin-12; adenosintrifosfát; Enzyme Activation; Hydrostatic Pressure; Caspase 8; Neoplasms; Tumor Necrosis Factor-alpha; Cell Line, Tumor; immunogenic cell death; proteiny tepelného šoku HSP70; reaktivní formy kyslíku; proteiny tepelného šoku HSP90; HSP70 Heat-Shock Proteins; regulační T-lymfocyty; fosforylace; Antigens, CD; dendritic cells; membránové proteiny; CD antigeny; fagocytóza; membránové glykoproteiny; HLA-DR Antigens; HMGB1 Protein; Interleukin-6; Membrane Proteins; kalretikulin; Phosphorylation; heat shock proteins; protein HMGB1; imunoglobuliny; dendritické buňky; Eukaryotic Initiation Factor-2; Calreticulin; antigen CD83; HSP90 Heat-Shock Proteins; stres endoplazmatického retikula; Reactive Oxygen Species; T-Lymphocytes, Regulatory; antigeny CD86; lidé; cancer immunotherapy; interleukin-6; Humans; hydrostatický tlak; Membrane Glycoproteins; B7-2 Antigen; aktivace enzymů; apoptóza; TNF-alfa; Phagocytosis; Adenosine Triphosphate; high hydrostatic pressure; nádory; Endoplasmic Reticulum Stress; kaspasa 8; nádorové buněčné linie; Dendritic Cells; Immunoglobulins; CD83 Antigen; interleukin-12; eukaryotický iniciační faktor 2; Apoptosis